The burden of proximal femur fractures and other skeletal injuries during the Covid-19 pandemic lockdown: a retrospective comparative study - Samaila, Elena Manuela; Negri, Stefano; Corzani, Marco; Zancan, Federico; Maluta, Tommaso; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Limiting people’s movement is one of the main preventive measures deployed for the control of coronavirus 2019‑nCoV pandemic. This study aims to assess the impact of COVID-19 lockdown on the incidence of the most common skeletal injuries and to provide a management algorithm specific for hospitalized fractured patients.We comparatively analysed the Emergency Department (ED) admissions between March 9th and May 4th 2020 with the same period in 2019. The frequency of the most common skeletal injuries has been derived. Data from the pre-hospitalization phase to discharge of all patients were considered. The impact on clinical orthopaedic consulting has been evaluated. All patients requiring orthopaedic care followed different pathways of hospitalization based on COVID positivity. Data of surgical activity has been analysed.During the 9 weeks of lockdown the access of patients to ED drastically decreased: 11726 accesses compared to 21501 in the same period of 2019. This trend was followed by the most common skeletal injuries but not by proximal femur fracture (PFF) that showed the same absolute numbers compare to the previous years (64 vs 63). If analysed in relation to the total ED access, PFF showed a relatively increase in their frequency.The data from this experience suggest that healthcare providers should strategically allocate resources for management and treatment of PFF during the COVID-19 pandemic. With the begin of the reopening phase, a “rebound effect” for orthopaedic care was observed leading to delayed treatments with a potential overall increased morbidity.